Human proteoforms as new targets for clinical mass spectrometry protein tests. (3rd August 2017) - Nedelkov, Dobrin
ABSTRACT: Introduction : Only about dozen mass spectrometry (MS) protein tests have been translated into clinical laboratories since the MALDI and ESI approaches were developed thirty years ago. While the cost and complexity of these assays are important factors impeding their clinical adoption, new content generated via proteoforms detection could provide the impetus for further development and translation. Areas covered : Provided here are several examples of MS-based protein assays capable of detecting proteoforms, including those for B-type natriuretic peptide (BNP) and parathyroid hormone (PTH). The evidence suggests that the ability to detect proteoforms is not enough to drive the clinical adoption of the MS-based tests – clinical utility of those proteoforms needs to be demonstrated first. Along those lines, recent efforts to discover, clinically validate, and initiate translation of novel proteoform biomarkers such as those of apolipoprotein C-III will be discussed. Expert commentary : MS protein tests face a challenging future. Both the sample preparation steps and the MS platforms need to be simplified to bring the cost per test down, and then the new content brought by the detection of proteoforms will drive the proliferation of these MS tests – first in clinical utility studies and then for routine diagnostics.